Divergent Effects of Nitrogen Addition on Soil Respiration in a Semiarid Grassland - Zhu, Cheng (Sci Rep, 2016)
Nitrogen (N) deposition has been steadily increasing for decades, with consequences for soil respiration. However, we have a limited understanding of how soil respiration responds to N availability. Here, we investigated the soil respiration responses to low and high levels of N addition (0.4 mol N m(−2) yr(−1) vs 1.6 mol N m(−2) yr(−1)) over a two-year period in a semiarid Leymus chinensis grassland in Inner Mongolia, China. Our results show that low-level N addition increased soil respiration, plant belowground biomass and soil microbial biomass carbon (MBC), while high-level N additions decreased them. Soil respiration was positively correlated with plant belowground biomass, MBC, soil temperature and soil moisture. Together plant belowground biomass and MBC explained 99.4% of variation in mean soil respiration, with plant belowground biomass explaining 63.4% of the variation and soil MBC explaining the remaining 36%. Finally, the temperature sensitivity of soil respiration was not influenced by N additions. Overall, our results suggest that low levels of N deposition may stimulate soil respiration, but large increases in N availability may decrease soil respiration, and that these responses are driven by the dissimilar responses of both plant belowground biomass and soil MBC.